Frame Approach to Teaching Foreign Students-Philologists. - Лагута, Т. Н.; Вержанская, О. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The importance of using a frame approach at linguistics classes in groups of foreign students-philologists has been proved theoretically in the article. The experience of using frames while teaching scientific speech has been analyzed. More than 20 frames to the basic concepts of linguistics have been created and implemented. The necessity of further development of the frames and their inclusion in the course “Introduction to Linguistics” for foreign students at the initial stage of training has been proved